ACTIVE MEDIA : Analysis of the possibility of fabricating compact combustion-driven DF lasers due to fuel preheating. (28th September 2016) - Xiaoting Fang,; Shengfu Yuan,; Weihong Hua,
Abstract: We report a theoretical calculation of the processes proceeding in the combustor of combustion-driven cw DF/HF chemical lasers with different mixtures of fuels preheated to high temperatures. Calculation results demonstrate a great effect of the preheating temperature on the yield of F atoms and strongest deactivator, on the primary dilution ratio ψp and on the estimated specific power. When fuels are preheated to about 1300 K, the specific power is improved by about 74.2%, and the total mass of the fuel is reduced by about 43%, which makes it possible to realise a more compact and efficient design of combustion-driven cw DF/HF chemical lasers at elevated combustor pressures. Fuel preheating can facilitate the development of chemical lasers and high-power lasers based not only on airborne and space-borne platforms, but also on mobile ground-based platforms.